PENDETEKSI KEBOCORAN GAS LPG MELALUI SMS GATEWAY DENGAN MENGGUNAKAN SENSOR MQ2 BERBASIS ARDUINO UNO - Missah, Wehellnimet junior; Hutabri, Ellbert (LPPM Universitas Putera Batam, 2022)
LPG is a liquidated natural fuel, often used in the industrial sector and also a necessity that facilitates the household environment sector, in the household itself we can not be separated from the use of LPG gas fuel (liquefied petroleum gas) inseparable from it also the use of LPG in the household sector and even the industry is very much, and that becomes a negative impact that arises as examples often we find in the media the existence of fires due to gas leaks, even we are not aware of a gas leak when we install gas on the switch so it is very dangerous when there is a fire trigger, Therefore, researchers designed an LPG gas leak detection tool via SMS Gateway using an Arduino uno based MQ2 sensor. This researcher designed a tool that serves to detect gas leaks and when there is a gas leak the tool will send a message to Whatsapp with the aim when the user is not in the area around the house or away from the use of gas then the tool will provide notification in the from of Whatsapp messages. Keyword: LPG gas detector, SMS Gateway, Whatsapp, Arduino Uno